The Use of QuillBot in Academic Writing: A Systematic Literature Review - Latifah, Siti; Muth’im, Abdul; Nasrullah, Nasrullah (Journey: Journal of English Language and Pedagogy, 2024)
In recent years, QuillBot, an AI-powered writing assistance tool, has gained significant attention within the academic writing sphere due to its innovative features to enhance productivity and improve the quality of written content. This study, employing the systematic literature review method, aims to explore the use of QuillBot in academic writing. A total of seventeen research publications published between 2018 and 2024 were included in this study. These articles were gathered from reliable databases such as Google Scholar, Semantic Scholar, ResearchGate, Emerald Insight Journals, Springer, ScienceDirect, and Taylor & Francis. The findings discovered that, while users value its time-saving features, concerns regarding overreliance and potentially hindering critical skills development exist. QuillBot significantly enhances writing quality and efficiency by detecting errors, paraphrasing, and expanding vocabulary. It also addresses language barriers and plagiarism concerns. Additionally, its function as a complement to autonomous writing and critical thinking was highlighted, and caution against over-reliance was suggested. Therefore, further research is needed to examine its influence on academic performance, effectiveness across linguistic contexts, and function in writing instruction.